QUALITY ASSESSMENT OF CURATIVE AND NUTRITIOUS DATE FRUCTOSE BISCUIT BAR - S. Bano; Salim-ur-Rehman; T. Zahoor; M. A. Sheikh (Journal of Animal and Plant Sciences, 2016)
The demand for enhanced nutrition value biscuits is increasing to curb malnutrition syndromes among children and aged peoples.  This study was undertaken to evaluate the effects of adding Indian vetch protein isolate and replacement of sucrose with date fructose on the physicochemical and sensory qualities of date fructose biscuit bars (DFBB).  Five treatments of date fructose biscuit bars were prepared with different levels of sucrose replacement with date fructose. Control treatment (T0) was prepared without date fructose and Indian vetch protein isolate.  The results revealed that addition of protein isolate and date fructose in biscuit bars contributed desirable hardness in texture and acceptable crispness. The bars were shelf stable due to low Aw.  Dark color was recorded in bars containing 20% date fructose than control. Gross energy values differed significantly among treatments. Mean values ranged from 3.49±0.1 to 4.34±0.2 Kcal/g. In-vitro starch digestibility ranged from 38.90±2.88 to 48.42±1.01mg maltose/g while in-vitro protein digestibility values also showed significant variation (P>0.05) among treatments. Biscuit bars containing 15% Indian vetch protein isolate and  15% sucrose replacement with date fructose were found the best in terms of physical and sensory characteristics.   Indian vetch protein isolates (IVPI) and date fructose could be utilized in biscuit bars as a cost effective diet to treat a target populace.
Keywords: biscuit bars; protein isolates; fructose; texture; water activity